2022
DOI: 10.1097/aud.0000000000001198
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Adaptation Recovery Function of the Auditory Nerve and Its Association With Advanced Age in Postlingually Deafened Adult Cochlear Implant Users

Abstract: Objective: This study aimed to (1) characterize the amount and the speed of recovery from neural adaptation at the auditory nerve (AN) and(2) assess their associations with advanced age in postlingually deafened adult cochlear implant users.Design: Study participants included 25 postlingually deafened adult, Cochlear Nucleus device users, ranging in age between 24.83 and 83.21 years at the time of testing. The stimulus was a 100-ms pulse train presented at four pulse rates: 500, 900, 1800, and 2400 pulses per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…Approaches for measuring eCAPs elicited by individual pulses of a constant-amplitude pulse train with a fixed or varied MPI have been reported in detail in our previous studies (He et al 2021a,b). Briefly, eCAPs in response to individual pulses of a pulse train were measured using a modified forward-masking technique (He et al 2017).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Approaches for measuring eCAPs elicited by individual pulses of a constant-amplitude pulse train with a fixed or varied MPI have been reported in detail in our previous studies (He et al 2021a,b). Briefly, eCAPs in response to individual pulses of a pulse train were measured using a modified forward-masking technique (He et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that adaptation during both phases is faster at higher pulse rates and varies substantially among patients (He et al 2021a). To evaluate adaptation recovery at the AN, the eCAP evoked by a probe pulse with a preceding pulse train masker at different MPIs is recorded (Dhuldhoya 2013; Adel et al 2017; Mussoi & Brown 2019; He et al 2021b). The amount of adaptation recovery can be quantified by comparing the eCAP amplitude measured at the longest MPI tested to the eCAP amplitude measured for the single-pulse stimulus that is presented at the same stimulation level (He et al 2021b).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations